(untitled) (FULafia Journal of Science and Technology, 2021)
This research focused on the lightning protective system (LPS) elements, most especially grounding using the elements of LPS as interceptor, down conductor and ground. Grounding is defined as a system of electrical fault save linkage to the earth and as a total set of measures used to connect an electrically conductive part to earth for equipment and life safety. The choice of Ikorodu town is informed by high voltage (HV) power transmission substations and heavy industries located in coastal area being affected by apparent isastrous lightning strike. The methodology used include collection of LPS network cross section sizes from 5 numbers of 33/11 kV distribution substations and one number of 132/33 kV Transmission substation in the study area. Also, the earthing resistance values of all the substations elements were collected. Physical measurements and existing design formula of previous work were used to evaluating the existing LPS network. Conductor size compliance ratio was also used for cross sectional area of down conductor, lightning electrode and air terminal adequacy.